Genome-wide association studies of viral infections—A short guide to a successful experimental and statistical analysis - Butković, Anamarija; Elena, Santiago F. (Frontiers in Systems Biology, 2022)
Genome-wide association studies (GWAS) have been gaining popularity over the last decade as they provide new insights into the genetic architecture of many disease-related traits. GWAS is based on the common disease common variant hypothesis, allowing identification of alleles associated with susceptibility and symptomatology of most common infectious diseases, such as AIDS, common cold, flu, and many others. It depends on the natural variation in a host population which can help identify genetic variants responsible for virus disease-related traits. Considering the prevalence of viruses in the ecosystem and their societal burden, identification of potential resistance loci or therapeutic targets is of great interest. Here, we highlight the most important points necessary for a successful GWAS of viral infectious diseases, focusing on the study design and various statistical methods used. Finally, we exemplify this application with studies done with human immunodeficiency virus type 1 and turnip mosaic virus.